Myelopathy: A rare presentation of initial systemic lupus erythematous manifestation in a young male - Ritu Gupta,; Deepak Warkade,; Sandeep Singh,; Piyush Varshney, (Indian Journal of Case Reports, 2020)
Acute transverse myelitis (ATM) is a consequence of inflammation of various etiologies resulting in damage to the nerve tracts. Regardless of the etiology, the prevalence of ATM is estimated at 1–4 new cases per million a year. Among connective tissue disorder, systemic lupus erythematous (SLE) is the most common cause of ATM. SLE is complicated by neurological manifestation in 25–80% of the patients. ATM may be a complication in 1–3% of SLE patients, but in some patients, it may be the first manifestation of SLE. We describe the case of a 20-year-old male where longitudinal extensive transverse myelitis was the initial manifestation of SLE involving almost the whole length of the spine. Early diagnosis and aggressive treatment may prevent long-term permanent damage and may have a favorable outcome